2016
DOI: 10.1093/nar/gkw1287
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-202 maintains spermatogonial stem cells by inhibiting cell cycle regulators and RNA binding proteins

Abstract: AbstractmiRNAs play important roles during mammalian spermatogenesis. However, the function of most miRNAs in spermatogenesis and the underlying mechanisms remain unknown. Here, we report that miR-202 is highly expressed in mouse spermatogonial stem cells (SSCs), and is oppositely regulated by Glial cell-Derived Neurotrophic Factor (GDNF) and retinoic acid (RA), two key factors for SSC self-renewal and differentiation. We used inducible CRISPR-Cas9 to knockout miR-202 in cultured SSCs, and found that the knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 57 publications
(61 reference statements)
7
97
1
Order By: Relevance
“…MiR-202-5p is a germ plasm unique miRNA that is abundantly enriched in the gonads of some mammals and lower vertebrates. In mouse, miR-202-5p is specifically expressed in the Sertoli cells of embryonic gonads [11] and in spermatogonial stem cells (SSCs) in the testis [12]. In human testis, miR-202-5p is a germ cell-dependent expressing miRNA in Sertoli cells [13], indicating its role in spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-202-5p is a germ plasm unique miRNA that is abundantly enriched in the gonads of some mammals and lower vertebrates. In mouse, miR-202-5p is specifically expressed in the Sertoli cells of embryonic gonads [11] and in spermatogonial stem cells (SSCs) in the testis [12]. In human testis, miR-202-5p is a germ cell-dependent expressing miRNA in Sertoli cells [13], indicating its role in spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, miR-202-5p is the predominant miRNA mature form expressed during testis differentiation and is expressed in somatic sertoli cells but not in germ cells [ 34 ]. In the adult mouse testis, miR-202-5p is enriched in sertoli cells, but both miR-202-5p and -3p mature forms are expressed in germ cells at similar levels [ 35 ]. Notably, knock-out (KO) of mir-202 in the mouse induces premature differentiation of spermatogonial stem cells and reduces stem cells activity, indicating that miR-202 is a key regulator of spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the global expression of miRNAs in the murine testis (Buchold et al, ; Hayashi et al, ; Jung et al, ; Ro, Park, Sanders, McCarrey, & Yan, ; Yan et al, ), but few examined miRNA abundance in specific testicular germ cell populations nor identified the functional importance of individual miRNAs during SSC homeostasis. Previous studies suggested that miR‐199a‐3p (Niu et al, ), miR‐106a (He et al, ), miR‐221 (Yang et al, ), and miR‐202 (Chen et al, ) play significant roles in SSCs. In this study, we showed that miR‐100 is predominantly expressed in undifferentiated mouse spermatogonia, particularly SSCs.…”
Section: Discussionmentioning
confidence: 99%